Combined antegrade and retrograde dilation (CARD) for management of complete esophageal obstruction: Multicenter case series - Hayat, Umar; Khan, Yakub I; Deivert, Duane; Obuch, Joshua; Altaf, Athar; Boger, John; Kamal, Faisal; Diehl, David L (Endoscopy International Open, 2024)
Background and study aims Complete esophageal obstruction (CEO) is a rare complication of radiation therapy for esophageal or head and neck cancers and can be challenging to manage endoscopically. A rendezvous approach by combined anterograde and retrograde endoscopic dilation (CARD) can be used to re-establish luminal integrity in such cases. Our study aimed to review our experience with patients with CEOs managed by CARD.Patients and methods Six patients who had CARD for CEO were reviewed. The primary outcomes were immediate technical and clinical success of CARD. Secondary outcomes were adverse events (AEs) associated with the procedure and continued dependency on the percutaneous endoscopic gastrostomy (PEG)-or jejunostomy tube.Results The mean age was 59 years (range 38–83). Five patients had CEO secondary to neoadjuvant chemoradiotherapy for esophageal cancer, and one patient had complete obstruction secondary to neck trauma. CARD was technically successful in five patients (86%). Two patients had AEs. One had pneumomediastinum requiring no intervention, while the other had bilateral pneumothorax requiring chest tube placement. The median follow-up duration of repeated dilations to maintain liminal patency was 20 months. Four patients had improvement in dysphagia, tolerating oral intake, and mouth secretions after the procedure, with a mean functional oral intake scale (FOIS) score > 3 and an overall success rate of 83%.Conclusions The CARD approach to re-establish esophageal luminal patency in CEO is a safer alternative to high-risk blind antegrade dilation or an invasive surgical approach. It is usually technically feasible with improved swallowing ability in most patients.
Keywords: Endoscopy Upper GI Tract; Malignant strictures; Benign strictures; Barrett's and adenocarcinoma